Teaching style, learning behaviour and learning achievement on economic education student of Universitas Negeri Padang - Eka Septianti Laoli; Efrizal Syofyan (Fakultas Ilmu Pendidikan UNP)
The background in this research is student achievement not yet reached the level of achievement maximal. Of which 74% of students have a GPA of <3.50. The purpose of this research is to analyze the effect of lecturer teaching style, and student learning behavior toward student achievement. This type of research is a quantitative descriptive. Population in this research is student of semester V of Economic Education Program of Universitas Negeri Padang which amounted to 124 people with propotional random sampling technique. The results showed that: 1) There is a positive and significant effect between teaching style lecturers and learning behaviour towards on the student achievement 2) There is a positive and significant effect between teaching styles lecturers towards on the student achievement, 3) There is a positive and significant effect between learning behaviour on student achievement.